A Prospective Randomised Double Blind Control Study to Find the Optimum Dosage of Nalbuphine as an Adjuvant to Spinal Anaesthesia - Priyanka Katoch; Naine Bhadrala; Kulbir Kour (Dr. Annil Mahajan, 2023)
Background: Adequate post-operative pain management is very important to facilitate the functional recovery and enable patients to rehabilitate fast to return to their normal activities. Major limitation is the fixed duration of action of local anesthetic which can be improved with adjuvant like (Opioid). Aim & Objectives: To find the onset and duration of sensory and motor block with different doses, and duration of post operative analgesia. Material & Methods: This is a prospective randomized double blind control study. 120 patients of ASA I & II physical status patients aged 20- 60 yrs under going lower abdominal and lower limb surgeries under subarachnoid block were allocated randomly to 4 groups A, B, C, D by lottery method. Group A Patients were given inj. Bupivacaine 2.5ml (H) +1ml N.S, Group B inj. Bupivacaine (H) 2.5 ml +0.4mg of Nalbuphine diluted to 1 ml of normal saline, Group C inj. Bupivacaine (H) 2.5ml +0.6mg of Nalbuphine diluted to 1 ml of normal saline, Group D inj. Bupivacaine (H) 2.5ml + 0.8mg of Nalbuphine diluted to 1 ml of normal saline. Results: Peak sensory level was significantly rapid in group D (0.8mg Nalbuphine) which is comparable to group C (0.6 mg Nalbuphine). The two-segment regression time of sensory block was statistically significant in group D &C. The time of onset of motor block to reach Bromage 3 was less in group D and C; statistically significant compared to Group A & B. Conclusion: The optimum dose of Nalbuphine to shorten the onset of sensory and motor block and prolong the duration of sensory and motor block and post-operative analgesia is 0.6mg without any increased side effects.